Design and Performance Enhancement of a Microstrip Patch Antenna for 2.4 GHz - ABDELOUAHAB GHRISSI; DJEGHBALA NASREDDINE (University of Shahid Hama Lakhdar - El Oued, 2025)
The field of wireless communications has witnessed rapid development in recent years, which necessitated the development of antennas capable of keeping up with the requirements of modern systems, in terms of performance, efficiency, and size. Among the most prominent of these antennas are Patch Antennas, which are characterized by light weight, ease of fabrication, low cost, and their ability to operate in multiple frequency bands with good radiation performance. This thesis aims to study, design, and analyze the performance of patch antennas using advanced simulation techniques. Emphasis was placed on analyzing basic antenna characteristics such as bandwidth, reflection coefficient (S11), and VSWR, as well as evaluating the impact of geometric modifications on the overall performance. HFSS software was used to perform accurate simulations of two designs: A conventional patch antenna and a modified patch antenna. The simulation results showed that the proposed modifications improved the radiation characteristics, making the modified design suitable for multiple applications such as Wi-Fi and IoT systemsparticularly those operating at 2.4GHz. شهد مجال الاتصالات اللاسلكية تطو اً ر متسارعًا خلال السنوات الأخيرة، مما استدعى تطوير هوائيات قاد رة على مواكبة متطلبات الأنظمة الحديثة، من حيث الأداء، الكفاءة، والحجم. ومن بين أبرز هذه الهوائيات نجد اله وائيات الرقعية ) Patch Antennas (، التي تتميز بخفة الوزن، سهولة التصنيع، وانخفاض التكلفة، إلى جانب قدرتها على العمل ضمن نطاقات تردد متعددة مع أداء إشعاعي جيد. تهدف هذه المذكرة إلى د ا رسة وتصميم وتحليل أداء الهوائيات الرقعية باستخدام تقنيات المحاكاة المتقدمة. تم التركيز على تحليل الخصائص الأساسية للهوائيات مثل عرض النطاق الترددي، معامل الانعكاس ) S11 (، ونسبة الموجات المرتدة ) VSWR (، بالإضافة إلى تقييم تأثير التعديلات الهندسية على الأداء العام. تم استخدام برنامج HFSS لإج ا رء محاكاة دقيقة لتصميمين: هوائي رقعي تقليدي وآخر معدل. أظهرت نتائج المحاكاة أن التعديلات المقترحة ساهمت في تحسين الخصائص الإشعاعية ، مما يجعل التصميم المعدل مناسبًا لتطبيقات متعددة مثل أنظمة Wi-Fi وانترنت الأشياء ) IoT ( وخاصة تلك التي تعمل بتردد 2,4GHz .
Master's theses: specializing in wired and non-wired communications.2025
Keywords: Patch antennas; HFSS; bandwidth; S11 reflection coefficient; VSWR; feeding techniques; antenna design.; الهوائيات الرقعية، HFSS ، عرض النطاق الترددي، معامل الانعكاس S11 ، VSWR ، تقنيات التغذية، تصميم الهوائيات